2016
DOI: 10.1530/rep-15-0287
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin promotes autophagy to protect primary human syncytiotrophoblasts from apoptosis

Abstract: Punicalagin is a prominent polyphenol in pomegranate juice that protects cultured syncytiotrophoblasts from stress-induced apoptosis. Here, we test the hypothesis that punicalagin has this effect by inhibiting the mTOR kinase pathway to enhance autophagic turnover and limit apoptosis in cultured primary human syncytiotrophoblasts. In syncytiotrophoblasts, starvation, rapamycin, or punicalagin all decreased the expression of phosphorylated ribosomal protein S6, a downstream target of the mTOR kinase, and of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
5
18
0
Order By: Relevance
“…Toward the end of pregnancy, preeclampsia is associated with high levels of placental autophagy, including the syncytiotrophoblast . The current results corroborate previous studies showing the activation of autophagy in in vitro models of human villous trophoblasts exposed to lower oxygen levels . As expected, the activation of the autophagic pathway was not modulated by melatonin in normoxia .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Toward the end of pregnancy, preeclampsia is associated with high levels of placental autophagy, including the syncytiotrophoblast . The current results corroborate previous studies showing the activation of autophagy in in vitro models of human villous trophoblasts exposed to lower oxygen levels . As expected, the activation of the autophagic pathway was not modulated by melatonin in normoxia .…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that hypoxic conditions led to activation of autophagy in human primary villous cytotrophoblasts . Beclin‐1 is a major activator of macroautophagy, referred herein simply as autophagy .…”
Section: Resultsmentioning
confidence: 99%
“…46 The downregulation of Prdx2 might promote apoptosis of cultured syncytiotrophoblasts or the reduced Prdx2 might influence the signal pathways that is involved in syncytialization. 14, 47 The exact reason is lack of evidences and need further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA of cell extracts for active, DNA-binding NF-κB (1007889, Caymen Chemical), and of culture supernatants for secreted CD14 (DY382, R&D Systems), secreted IL-6 (DY206, R&D Systems), secreted IL-8 (DY208, R&D Systems) and secreted TNF-α (DY201, R&D Systems) were performed according to the manufacturer's instructions. hCG ELISA were performed as described previously (Chen et al 2016).…”
Section: Elisamentioning
confidence: 99%